Comparison of Environmental Attitudes of Students Attending Adiwiyata Schools and Non-Adiwiyata Schools - Ravika Febriza Martias Putri; Efni Cerya (JRTI (Jurnal Riset Tindakan Indonesia), 2025)
Environmental issues have become an alarming global problem, this is motivated by the low environmental awareness of the community. To overcome this, the government made a policy in the form of implementing the adiwiyata program at various school levels. The implementation of the adiwiyata program aims to create a caring attitude towards the environment from an early age through formal education. This study aims to assess the effectiveness of the implementation of the adiwiyata policy in fostering an attitude of environmental care, as well as analyzing whether there are differences in the environmental care attitudes of students in adiwiyata schools and non-adiwiyata schools. This research is a quantitative research with a comparative approach. The research was conducted using a questionnaire consisting of positive and negative statements about environmental care attitudes, where each statement contains answers with Likert scale values of 1 to 4. The sampling technique in this study refers to the provisions of the sample size according to Abubakar (2021), with a total sample size in each school of 30 students. The data analysis technique used Paired Sample T-Test with the SPSS version 15. The research was conducted at SMPN 1 Luhak Nan Duo as an Adiwiyata School and SMPN 3 Luhak Nan Duo as a Non-Adiwiyata School. The results showed that the environmental care attitude of students in Adiwiyata School was classified as good with an average score of 82.81. The attitude of environmental care of students at SMPN 3 Luhak Nan Duo is also classified as good with an average score of 78.45. Although both schools get the title of a good caring attitude, the results of the comparison test show that there is a significant difference in the attitude of environmental care between students who attend Adiwiyata Schools and Non Adiwiyata Schools.